Cytological and complete blood count profile in a dog with suspected skin tumours - Chika Khaerani Mutiara; Stevanie Andrea Wijaya; Aditya Gilang Prasaja; Septiani Purwanti Hanafiah; Fransiskus Teguh Santoso; Sarasati Windria (ARSHI Veterinary Letters, 2024)
Skin tumours are among the most prevalent neoplasms in older dogs, and often display diverse clinical signs. This case report outlines the clinical presentation, diagnosis, and treatment of a suspected skin tumour in a 10-year-old obese female Golden Retriever weighing 46 kg. The owner brought the dog to West Java Provincial Animal Hospital with mandibular swelling, decreased appetite, and tachypnoea. Physical examination revealed a rectal temperature of 40.1°C, painful mandibular swelling, respiratory rate of 236 breaths per minute, and heart rate of 88 beats per minute. Cytology revealed pleomorphism, coarse chromatin, and nuclear moulding, suggesting increased cellular activity. Haematological results showed leukocytosis, granulocytosis, and hyperchromic normocytic anaemia, likely due to the release of proinflammatory cytokines from the tumour and immune cells. Differential diagnosis included sialadenitis, apocrine gland tumours, and salivary gland adenocarcinoma. The final diagnosis was skin tumour with poor prognosis. The treatment involved iron dextran, supplements, dexamethasone, sulfadiazine-trimethoprim, cyproheptadine HCl, and tolfenamic acid